2020
DOI: 10.1177/0004944120947881
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mathematics anxiety on self-regulated learning and mathematical literacy

Abstract: Self-regulated learning has been shown to have a positive and long-lasting impact on students’ academic development, employability and career progression. Emotions, motivation and metacognition play an important role in students’ ability to monitor and regulate their learning, particularly when studying and engaging with Science, Technology, Engineering and Mathematics content. In this study, we investigated motivational, emotional and cognitive factors involved in self-regulated learning and their role in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 52 publications
(85 reference statements)
2
37
0
2
Order By: Relevance
“…It is unclear how negative mathematics beliefs could be related to mathematics anxiety and mathematics performance. However, one explanation could be that metacognitive processes mediate the relationship between negative mathematics beliefs and mathematics performance, as reported in several studies (for discussion see Legg and Locker Jr, 2009;Filippello et al, 2016;Buzzai et al, 2020;Gabriel et al, 2020). Future research should investigate the exact mechanism of how beliefs, metacognition, and mathematics performance interact.…”
Section: Factors Underlying Mathematics Anxietymentioning
confidence: 86%
“…It is unclear how negative mathematics beliefs could be related to mathematics anxiety and mathematics performance. However, one explanation could be that metacognitive processes mediate the relationship between negative mathematics beliefs and mathematics performance, as reported in several studies (for discussion see Legg and Locker Jr, 2009;Filippello et al, 2016;Buzzai et al, 2020;Gabriel et al, 2020). Future research should investigate the exact mechanism of how beliefs, metacognition, and mathematics performance interact.…”
Section: Factors Underlying Mathematics Anxietymentioning
confidence: 86%
“…Florence Gabriel shares the latest thinking on dealing with "maths anxiety" Education where we investigated the ways in which maths anxiety impacts mathematical achievement in high-school students. 5 We analysed data from the OECD's Programme for International Student Assessment and looked at the responses of more than 4,000 Australian 15-year-old students. Our study showed that higher levels of maths anxiety are associated with lower levels of instrumental motivation (the degree to which students find mathematics relevant), self-concept (students' beliefs in their own abilities in mathematics), perseverance (students' willingness to keep working on difficult problems), and selfefficacy (students' beliefs about their ability to solve specific maths problems).…”
Section: Maths Anxiety -And How To Overcome Itmentioning
confidence: 99%
“…Using logical reasoning means that these students are able to choose the right strategy in solving a problem. Therefore, this ability becomes a point in developing students' abilities in the 21st century as a provision for solving problems in everyday life (Gabriel et al, 2020;Ülger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%